2019
DOI: 10.1186/s12903-019-0712-x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for tooth loss during supportive periodontal therapy in patients with severe periodontitis: a Japanese multicenter study

Abstract: BackgroundSupportive periodontal therapy (SPT) must take individual patient risk factors into account. We conducted a multicenter joint retrospective cohort study to investigate the value of modified periodontal risk assessment (MPRA) and therapy-resistant periodontitis (TRP) assessment as predictive factors for tooth loss due to periodontal disease in patients with severe periodontitis during SPT.MethodsThe subjects were 82 patients from 11 dental institutions who were diagnosed with severe periodontitis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
(56 reference statements)
0
9
0
1
Order By: Relevance
“…Retrospective studies were performed based on patient charts at dental schools in Canada where a Dalhousie study reported a mean TLP of 0.06/patient/year (Matthews, Smith, & Hanscom, 2001) and one in Manitoba reported a mean TLP of 0.016/patient/year (Fisher et al, 2008). A Japanese multisite university-based study calculated a mean of 0.040 TLP/patient/year among PMT compliant patients (Hirata, Fuchida, Yamamoto, Kudo, & Minabe, 2019). These three studies found smoking to not be associated with TLP.…”
mentioning
confidence: 99%
“…Retrospective studies were performed based on patient charts at dental schools in Canada where a Dalhousie study reported a mean TLP of 0.06/patient/year (Matthews, Smith, & Hanscom, 2001) and one in Manitoba reported a mean TLP of 0.016/patient/year (Fisher et al, 2008). A Japanese multisite university-based study calculated a mean of 0.040 TLP/patient/year among PMT compliant patients (Hirata, Fuchida, Yamamoto, Kudo, & Minabe, 2019). These three studies found smoking to not be associated with TLP.…”
mentioning
confidence: 99%
“…In addition, other prognostic factors such as bone loss/age ratio, number of teeth lost, and comparison with other prognostic tools such as periodontal risk assessment and therapy-resistant periodontitis assessment warrant investigation in future. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…Multiple tooth loss in older people is the cumulative result of dental caries and periodontal diseases that have occurred throughout their lives [ 8 , 9 ]. To restore oral functions hindered by multiple tooth loss, costly dental prosthetic services, such as dentures and dental implants, are needed.…”
Section: Introductionmentioning
confidence: 99%